POР-UP STORE AS A REPLACEMENT (FLEXIBLE) TRADE MODEL - Поневатель, Атилла (SWorldJournal, 2021)
The work discusses a model that ensures the continuity (flexibility) of modern trade. The quality of turnover (flexibility) here is due to the increasing tendency to move from rigid to dynamic business activities related to the sale of goods use temporary